Achieving Financial Well-Being & Sustainability for B40 Group: A Case Study of People’s Housing Program (PPR) Mumpreneurs - Mohamad Fuzi, Amirah; Mohd Noor, Nurul Hidayana (Journal of Social Transformation and Regional Development, 2024)
Most of the women from the B40 groups have been involved in informal business. Many mumpreneurs need higher knowledge, education, motivation, imbalance between work and household roles, and financial restraint in developing a business. Therefore, the objective of this study is determined based on the level of bankability status among B40 managers and to assess the issue of financial management, which could affect their bankability and business expansion. This study uses a qualitative method, and the research instrument used is a semi-structured interview. The data were analyzed using descriptive and inductive techniques. The study involved 23 respondents who are B40 mumprenuers who live in PPR Kerinchi Lembah Pantai. Thematic analysis is employed to analyze, identify, and report themes and patterns in the research data. The analysis is done by combining approaches: 1) descriptive approach and 2) inductive (data-driven) approach. The findings revealed that the level of bankability among mumprenuers is low. Second, the results of the inductive approach revealed that most of the mumpreneurs practicing poor financial management could affect their business’s sustainability. The implication is that mumpreneurs still need continuous disclosure and awareness in managing their finances, especially in cash inflow and outflow, budgeting, and decision-making.